PREPARING WOMEN FOR SAFE PREGNANCY, CHILDBIRTH, AND THE BIRTH OF A HEALTHY BABY: A COMMUNITY EMPOWERMENT PROGRAM - Dewi, Ratna Sari; Purwanti, Tri (Library Unit collaborates with the Institute for Research and Community Service, College of Health Sciences Husada Jombang, 2025)
Community service activities aimed at preparing women for healthy pregnancies and childbirth were conducted in Jombang Regency in April 2025. The program was initiated due to the ongoing need for education on preconception and prenatal care to reduce maternal and neonatal complications. The objectives included enhancing the understanding of preconception counseling, preparation for safe childbirth, recognition of healthy pregnancy signs, and the importance of antenatal check-ups. Activities involved health education sessions using PowerPoint presentations, distribution of leaflets, and interactive discussions. A total of participants, including late adolescents, prospective brides, and women of reproductive age, attended. Evaluations through pretests and posttests indicated a 35% improvement in knowledge. The program successfully raised awareness and encouraged participants to regularly seek health services for preconception and prenatal care.